Are hippocampal size differences in posttraumatic stress disorder mediated by sleep pathology?. (1st June 2014) - Mohlenhoff, Brian S.; Chao, Linda L.; Buckley, Shannon T.; Weiner, Michael W.; Neylan, Thomas C.
Abstract: Posttraumatic stress disorder (PTSD) is associated with smaller volumes of the hippocampus, as has been demonstrated by meta‐analyses. Proposed mechanistic relationships are reviewed briefly, including the hypothesis that sleep disturbances mediate the effects of PTSD on hippocampal volume. Evidence for this includes findings that insomnia and restricted sleep are associated with changes in hippocampal cell regulation and impairments in cognition. We present results of a new study of 187 subjects in whom neither PTSD nor poor sleep was associated with lower hippocampal volume. We outline a broad research agenda centered on the hypothesis that sleep changes mediate the relationship between PTSD and hippocampal volume.